The road to Neverwinter - Johnson, Jaleigh (Random House Worlds, 2023)
Imagines the original quest of the adventuring party of Edgin Darvis and his team of occasionally heroic heisters in an official prequel to the upcoming film Dungeons & Dragons: Honor Among Thieves.